Catholicism, sexual deviance, and Victorian Gothic culture - O'Malley, Patrick R. (Cambridge studies in nineteenth-century literature and culture ;, 2006)
It has long been recognised that the Gothic genre sensationalised beliefs and practices associated with Catholicism. Often, the rhetorical tropes and narrative structures of the Gothic, with its lurid and supernatural plots, were used to argue that both Catholicism and sexual difference were fundamentally alien and threatening to British Protestant culture. Ultimately, however, the Gothic also provided an imaginative space in which unconventional writers from John Henry Newman to Oscar Wilde could articulate an alternative vision of British culture. Patrick O'Malley charts these developments from the origins of the Gothic novel in the mid-eighteenth century, through the mid-nineteenth-century sensation novel, toward the end of the Victorian Gothic in Bram Stoker's Dracula and Thomas Hardy's Jude the Obscure. O'Malley foregrounds the continuing importance of Victorian Gothic as a genre through which British authors defined their culture and what was outside it.